Robotic vs open distal pancreatectomy: A multi‐institutional matched comparison analysis. (3rd February 2021) - Magistri, Paolo; Boggi, Ugo; Esposito, Alessandro; Carrano, Francesco Maria; Pesi, Benedetta; Ballarin, Roberto; De Pastena, Matteo; Menonna, Francesca; Moraldi, Luca; Melis, Marcovalerio; Coratti, Andrea; Newman, Elliot; et al.
Abstract: Background: Pancreatic surgery is still a challenge even in high‐volume centers. Clinically relevant postoperative pancreatic fistula (CR‐POPF) represents the greatest contributor to major morbidity and mortality, especially following pancreatic distal resection. In this study, we compared robotic distal pancreatectomy (RDP) to open distal pancreatectomy (ODP) in terms of CR‐POPF development and analyzed oncologic efficacy of RDP in the subgroup of patients with pancreatic ductal adenocarcinoma (PDAC). Methods: We collected data from five high‐volume centers for pancreatic surgery and performed a matched comparison analysis to compare short and long‐term outcomes after ODP or RDP. Patients were matched with a 2:1 ratio according to age, ASA (American Society of Anesthesiologists) score, body mass index (BMI), final pathology, and TNM (Tumour, Node, Metastasis) staging system VIII ed . Results: Two hundred and forty‐six patients who underwent 82 RDPs and 164 ODPs were included. No differences were found in the incidence of CR‐POPF. In the PDAC group, median DFS and OS were 10.8 months and 14.8 months in the ODP group and 10.4 months and 15 months in the RDP group, respectively. Conclusions: Robotic distal pancreatectomy is a safe surgical strategy for PDAC and incidence of CR‐POPF is equivalent between RDP and ODP. RDP should be considered equivalent to ODP in terms of oncological efficacy when performed in high‐volume and proficient centers. Abstract : Highlight In this multicenter matched comparison analysis, Magistri and colleagues revealed that robotic distal pancreatectomy significantly reduced postoperative hospital stay, with equivalent incidence of clinically relevant pancreatic fistula, and similar survival rates in the adenocarcinoma subgroup, compared with open distal pancreatectomy. Robotic distal pancreatectomy is safe in patients with left‐sided pancreatic neoplasms.